2016
DOI: 10.1364/oe.24.030350
|View full text |Cite
|
Sign up to set email alerts
|

Pre-equalization technique enabling 70 Gbit/s photonic-wireless link at 60 GHz

Abstract: In this paper, we demonstrate a 70 Gbit/s photonic-based wireless link at 60 GHz using a single RF carrier and a single polarization. This high capacity is achieved by using 32QAM modulation with a symbol rate of 14 GBd. We show a novel pre-equalization technique that enables usage of such very high bandwidths at 60 GHz. Our work indicates that the consumer oriented 60 GHz band could be a viable alternative to more expensive E-band or sub-THz links for high capacity photonic wireless transmission, mobile backh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Employing a highly efficient wireless backhaul service by connecting multiple base stations with small cell size will ensure high data rate to the end users [38]. Thus, enabling photonics based wireless links (millimeter to THz frequency band) offers high efficiency and cost-effective solution to the mobile backhauling and 'last mile' connections [39][40][41]. Similarly, the THz communication systems can be used to establish short range high-speed wireless links for applications such as chip-to-chip communications, KIOSK downloading, high-speed indoor wireless LAN to name a few [42].…”
Section: Introductionmentioning
confidence: 99%
“…Employing a highly efficient wireless backhaul service by connecting multiple base stations with small cell size will ensure high data rate to the end users [38]. Thus, enabling photonics based wireless links (millimeter to THz frequency band) offers high efficiency and cost-effective solution to the mobile backhauling and 'last mile' connections [39][40][41]. Similarly, the THz communication systems can be used to establish short range high-speed wireless links for applications such as chip-to-chip communications, KIOSK downloading, high-speed indoor wireless LAN to name a few [42].…”
Section: Introductionmentioning
confidence: 99%
“…If that is the case, then the maximum OSSR achievable is approximately equal to the extinction ratio (ER) of the optical modulator [23]. For amplitude and phase channel response corrections, a digital pre-equalization technique such as the one presented in [24] can be used. For time-matching, two phase shifters may be placed in each electrical arm of the IQ-modulator.…”
Section: Generation Of Spectrally-efficient Thz Ssb Signals Throumentioning
confidence: 99%
“…Using a bit-rate R b of 8 Gb/s, 4 channels, and 3 sectors, the aggregated capacity is 96 Gb/s. Recent research has shown even higher bitrates at millimeter wave frequencies, but mostly for point-to-point communication [17]- [22]. Yet, one of the main limiting factors for NG RAN at millimeter wave frequencies is the increased free space path loss that either reduces the reach of the access network or forces the utilization of beam steering systems.…”
Section: A Millimeter Wave Communicationsmentioning
confidence: 99%